PENGARUH PELAYANAN PERPUSTAKAAN SEKOLAH TERHADAP MINAT BACA SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 TAPA KECAMATAN TAPA KABUPATEN BONE BOLANGO - Abd Sigit Talani; Agil Bahsoan; Mamang Kasim; Melizubaida Mahmud; Cristian Polamolo (Yayasan Pendidikan Sudirman Mandiri, 2026)
This study aims to determine the effect of school library services on students' reading interest in economics at SMA Negeri 1 Tapa, Bone Bolango Regency. Thesis, Bachelor of Economics Education Study Program, Department of Education, Gorontalo State University. The data source for this study is primary data. The data collection technique was through the distribution of questionnaires. The population in this study was 165 students, while the sample in this study was 41 students. Data were analyzed using simple linear regression. The results of this study indicate that school library services have an effect on students' reading interest in economics at SMA Negeri 1 Tapa, Bone Bolango Regency. The Pearson correlation coefficient value obtained was 0.351. This indicates that library services exist at SMA Negeri 1 Tapa, Bone Bolango Regency, while the remaining 35.1% is influenced by other variables not examined in this study.